Homeownership and Entrepreneurship: The Role of Commitment and Mortgage Debt - Philippe Bracke; Christian Hilber; Olmo Silva (Institute for the Study of Labor (IZA), 2013)
We study the link between homeownership and entrepreneurship using a model of occupational choice and housing tenure where homeowners commit a fixed budget to mortgage payments. Our model predicts that: (i) mortgage commitments, by amplifying risk aversion, diminish the likelihood that homeowners start a business; (ii) the negative link between homeownership and entrepreneurship is increasing in mortgage debt; and (iii) the negative relation is more pronounced for entrepreneurs in risky sectors. Exploiting the longitudinal dimension of the British Household Panel Survey to control for unobservables, we test and confirm these predictions. Leveraged home-buyers are 30% less likely to become entrepreneurs.
Keywords: L26; D14; G11; R21; 330; entrepreneurship; homeownership; commitment